2005
DOI: 10.1111/j.1464-410x.2005.05733.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the secreted form of clusterin protein in renal cell carcinoma as a predictor of disease extension

Abstract: were evaluated in relation to several clinicopathological factors. RESULTSThere were various levels of clusterin expression in 128 of the 131 RCC specimens, while 37 of 131 normal kidney tissues (28.2%) had no clusterin staining. Clusterin protein was present in the cytoplasm of both normal and cancer cells, but there was no nuclear staining identified in either type of cell. The expression level of clusterin protein in RCC tissues was significantly related to tumour stage and grade, but not to age, gender or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 20 publications
3
39
1
Order By: Relevance
“…Although this study showed an association between high cytoplamic clusterin and adverse outcome for stage II colorectal cancer, there are conflicting data regarding the prognostic importance of this protein in different cancer types (17)(18)(19)(20)(21)(22)(23); some studies associate high clusterin levels with poor outcome (17)(18)(19)(20)(21) and others with a good prognosis (22,23). This may be related to a number of clinical and technical factors.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 82%
See 1 more Smart Citation
“…Although this study showed an association between high cytoplamic clusterin and adverse outcome for stage II colorectal cancer, there are conflicting data regarding the prognostic importance of this protein in different cancer types (17)(18)(19)(20)(21)(22)(23); some studies associate high clusterin levels with poor outcome (17)(18)(19)(20)(21) and others with a good prognosis (22,23). This may be related to a number of clinical and technical factors.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 82%
“…Several studies have examined the prognostic significance of clusterin in human cancer with conflicting results. Cytoplasmic clusterin expression correlates with poor prognosis in prostate adenocarcinoma (17), renal cell carcinoma (18), ovarian carcinoma (19), cervical cancer (20), and hepatocellular carcinoma (21). In contrast, cytoplamic clusterin expression correlates with a good prognosis in pancreatic adenocarcinoma (22) and non-small cell lung cancer (23).…”
Section: Introductionmentioning
confidence: 96%
“…Immunohistochemical staining. In cases diagnosed as having micrometastases according to real-time RT-PCR, despite the lack of positive findings on routine pathologic examinations, sections adjunct to the site of the original sections for H&E staining were cut from the original formalin-fixed, paraffin-embedded blocks, and examined to determine whether occult foci of prostate cancer cells were present by immunohistochemical staining with a monoclonal antibody against PSA (Dako, Carpinteria, CA) using standard immunohistochemical techniques as reported previously (16). After staining, the sections were counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic and predictive [20] value of CLU has already been evaluated in various malignancies, but conflicting results have been reported [6][7][8][9][21][22][23][24]. Conflicting data on the levels of CLU in lung cancer have also been found.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, CLU has been found to be involved in various physiologic processes important for carcinogenesis and tumor growth, including apoptotic cell death, cell cycle regulation, DNA repair, tissue remodeling, lipid transportation, membrane recycling, and immune system regulation [3][4][5]. Several studies have examined the prognostic value of CLU in various malignancies, with conflicting results [6][7][8][9]. Only one study investigated the prognostic role of CLU in a heterogeneous series of resected NSCLC, and the results suggested that CLU expression could be a positive prognostic indicator for NSCLC [10].…”
Section: Introductionmentioning
confidence: 99%